Gastric lavage for prevention of feeding problems in neonates with meconium-stained amniotic fluid: a randomised controlled trial. (May 2014) - Sharma, Preeti; Nangia, Sushma; Tiwari, Soumya; Goel, Ankita; Singla, Bhupesh; Saili, Arvind
Abstract : Background: The role of gastric lavage in preventing retching, vomiting and secondary meconium aspiration syndrome in neonates with meconium-stained amniotic fluid is uncertain, and no there are no definitive guidelines. Objective: To evaluate the effect of gastric lavage in preventing retching, vomiting and secondary meconium aspiration syndrome in neonates with meconium-stained amniotic fluid. Methods: This was an open-label, parallel, randomized controlled trial conducted in the labour room, postnatal and neonatal wards of a tertiary-care teaching hospital. Vigorous neonates of ≧34 weeks gestation with meconium-stained amniotic fluid were randomised into two groups using block randomisation. Infants requiring oxygen, in respiratory distress or with major congenital malformations were excluded. Infants in the study group received elective gastric lavage in the labour room after initial stabilisation. No gastric lavage was done in the control group. The newborns were assessed for retching, vomiting and secondary meconium aspiration syndrome in the first 48 hrs of life or until discharge from the hospital, whichever was later. Results: A total of 267 newborns were randomly assigned to the gastric lavage group and 269 to the no gastric lavage group. There were no statistical differences in overall feeding between the two groups (6·74% vs 10·78%). Feeding of two newborns in the no-lavage group had to be omitted for the initial few hours because of vomiting; this did not happen in any newborn in the lavage group. No newborn in either group developed secondary meconium aspiration syndrome. Conclusion: Gastric lavage in newborns with meconium-stained amniotic fluid does not prevent or reduce the occurrence of feeding problems or secondary meconium aspiration syndrome.